Author Correction: Development and validation of a risk prediction model for work disability: multicohort study. Issue 1 (December 2018) - Airaksinen, Jaakko; Jokela, Markus; Virtanen, Marianna; Oksanen, Tuula; Pentti, Jaana; Vahtera, Jussi; Koskenvuo, Markku; Kawachi, Ichiro; Batty, G.; Kivimäki, Mika
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has not been fixed in the paper.